Hospital Performance and Health Quality Improvements in São Paulo (Brazil) and Maryland (USA) - Medici, Andre (World Bank, Washington, DC, 2012)
Hospitals are the most essential and most costly component of health systems. They account for up to two-thirds of health spending. As a result, they greatly influence the overall quality of health care. As governments search for the best ways to monitor and evaluate hospital performance, policy-makers must identify the best ways to maximize hospital outcomes, patient satisfaction, and operational efficiency. Recent increases in healthcare costs have generated a number of proposals for the organization of publicly financed hospitals. These include new management models, new payment systems and clinical guidelines and disease treatment protocols inspired by evidence-based guidelines.